Unizentrische, retrospektive Analyse der praktischen Durchführung der extrakorporalen Photopherese: periphervenöser und zentralvenöser Zugang im Vergleich = Single-center retrospective analysis of extracorporal photopheresis in clinical practice : peripheral venous compared to central venous access - Hambsch, Jasmin; Büttner, Sylvia; Nicolay, Jan Peter; Felcht, Moritz; Booken, Nina; Klemke, Claus-Detlev (Der Hautarzt, 2019)
BackgroundExtracorporal photopheresis (ECP) was shown to be effective without severe side effects in the treatment of cutaneous T cell lymphoma (CTCL) and graft versus host disease (GvHD). However, only few studies investigated the practical aspects of ECP.MethodsTreatment protocols of 2038 ECP procedures in 52 patients (CTCL, n = 29; GvHD, n = 15; other, n = 8) were evaluated. The patients were treated with the UVAR® XTS™ ECP system (Therakos, Inc. Johnson & Johnson, Raritan, NJ, USA) between 2001 and 2010. All patients started with a peripheral venous access. During the course of treatment 7 patients were treated via a port and 4 via a central venous catheter.ResultsIn all, 1765 (86.6%) treatments were performed with a peripheral venous access; 239 (11.7%) ECPs were done via a port and 34 (1.7%) via a central venous catheter. The peripheral venous access showed a higher flow rate and longer photoactivation time. ECPs via port lead to higher UV-irradiated volumes, longer treatment times and higher differences in systolic blood pressure. The following side effects were observed: being unwell (n = 13), hypo- (n = 13) and hypertension (n = 7), vertigo (n = 4), headache (n = 4), shortness of breath (n = 4), fever (n = 3) and metallic taste (n = 3). Technical complications such as problems with venous access (9.6%) occurred in 385 (18.9%) treatments.ConclusionsPeripheral venous access should be preferred for ECP treatments.
Gesehen am 14.05.2019